Model Perbaikan Implementasi Aplikasi “Lansia Sehat” sebagai Strategi Penguatan Tata Kelola Program Kesehatan Lansia di Kabupaten Tanggamus - Dewi Ajeng Widyawati; Risky Kusuma Hartono (Institut Nalanda, 2026)
Introduction: The Lansia Sehat application was developed as a recording and reporting system for elderly health services. However, its utilization at the service level has not been optimal. This study aimed to evaluate the implementation of the Lansia Sehat application in Tanggamus Regency from a health management perspective. Methods: This study used a qualitative design with a case study approach. Informants included elderly program managers, primary healthcare staff, and related application users. Data were collected through in-depth interviews, observations, and document reviews. Data analysis was conducted using the Input–Process–Output (IPO) framework. Results: The application implementation was not optimal, indicated by double recording practices and limited data use for reporting purposes only. In the input aspect, issues included limited interface design, absence of integrated user guidance, lack of offline features, and weak operational policy support. In the process aspect, data entry was inefficient, the system was not integrated, and synchronization problems frequently occurred. In the output aspect, the application improved report standardization, but the speed, accuracy, and use of data for decision-making remained low. Conclusion: The application is still in a transitional phase and has not produced significant managerial impact. Required improvements include simplification of data entry workflows, provision of integrated user guidance, addition of offline features with automatic synchronization, and integration with other reporting systems to reduce duplicate recording. Strengthening governance, improving system design, clarifying roles, and optimizing data utilization are required to transform the application into a decision-support system for elderly health programs.